Algorithm for estimating Cr coating thickness for accident tolerant fuel cladding using a pancake ECT sensor - Jeong Won Park; Daegyun Ko; Hun Jang; Hoyoung Kim; Jaebeom Lee; Wonjae Choi (Nuclear Engineering and Technology)
The accident-tolerance of nuclear fuel rods has been a topic of continued interest since the Fukushima disaster. A notable advance in this area involves the development of Cr-coated nuclear fuel rods. This coating confers several benefits compared with conventional HANA-6 fuel rods, including superior corrosion resistance, enhanced durability, and increased thermal efficiency. The efficacy of the Cr coating is contingent upon maintaining an optimal thickness, which necessitates precise measurement technologies. In this context, the present study employs the eddy current testing (ECT) technique to ascertain the thickness of the Cr coating on nuclear fuel rods. A pancake ECT sensor was designed and fabricated to conduct thickness measurements in the confined spaces of multiple fuel assemblies. Nuclear fuel rods of various thicknesses were manufactured, and the thicknesses of the nuclear fuel rods were measured using a destructive method to provide the standard thickness for ECT measurement. Selection of the optimal frequency was driven by analysis of the measurement signals, and a dedicated algorithm for thickness measurement was subsequently formulated based on these findings. The application of this algorithm to predict the coating thickness in 10 out of 30 specimens demonstrated high accuracy without prior knowledge of conductivity of the materials.